2013
DOI: 10.1024/1661-4747/a000169
|View full text |Cite
|
Sign up to set email alerts
|

Evidenzbasierte Patienteninformationen im Internet – Eine Studie zur Qualität von Websites zur Posttraumatischen Belastungsstörung

Abstract: Weite Teile der Bevölkerung informieren sich bei Fragen zu psychischer Gesundheit im Internet. Dabei beeinflussen die dort recherchierten Informationen Gesundheitsverhalten und -einstellungen. Umso wichtiger ist es, die Qualität medizinischer und psychologischer Internetinformationen sicher zu stellen und auf ihre Hochwertigkeit auch im Sinne der Evidenzbasierung hin zu überprüfen. Im internationalen Raum existiert eine Reihe von Studien, die Mängel an der Qualität internetbasierter Gesundheitsinformationen ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…Therefore, despite the established benefits of online health services such as the empowerment of patients [20], searching online health sites may carry a risk of aggravating health anxiety and lead to dysfunctional health behaviors such as doctor hopping, ordering nonprescribed medicine online, or intensifying their online research. However, studies show that the quality of information in health websites is often questionable [21]. As a consequence, individuals may have difficulties differentiating between reliable websites and websites with less reliable information.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite the established benefits of online health services such as the empowerment of patients [20], searching online health sites may carry a risk of aggravating health anxiety and lead to dysfunctional health behaviors such as doctor hopping, ordering nonprescribed medicine online, or intensifying their online research. However, studies show that the quality of information in health websites is often questionable [21]. As a consequence, individuals may have difficulties differentiating between reliable websites and websites with less reliable information.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the quality of health websites often seems questionable. By way of example, Eichenberg, Blokus, & Malberg [10] evaluated German-speaking websites providing information about posttraumatic stress disorder. They found that information quality was heterogeneous, often due to low usability.…”
Section: Introductionmentioning
confidence: 99%
“…doctor hopping, ordering non-prescribed medicine online or intensifying their online research). Unfortunately, studies show that information quality of health websites is often questionable [19]. As laymen might have difficulties differentiating between websites with low and high reliability it seems important to minimize misleading information on the internet.…”
Section: Discussionmentioning
confidence: 99%